Manajemen Strategi Badan Narkotika Nasional Kabupaten (BNNK) dalam Penanggulangan Narkoba di Ranah Pendidikan Karawang - Budi Abdurrakhman; Hanny Purnamasari; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2021)
This article talks about the strategy of the Karawang Regency National Narcotics Agency (BNNK) in dealing with drug trafficking and abuse in the education sector wich is so massive. This type of research is descriptive qualitative by making BNNK Karawang as the research subject. The sampling technique is done through non-probillity sampling and snow ball sampling. Meanwhile, the data were obtained through tringulation (interviews, obcervation and documentation). The theory used is Fred R. David strategic management. The results of this study indicate that the high rate of drug abuse among students as a result of Karawang which is a large target market for drug dealers, thus making BNNK Karawang very difficult to find the right formula to overcome this. Implementation is carried out optimally but is still constrained by the lack of facilities and evaluation is always carried out by inviting all elements of society create an optimization strategy carried out by BNNK Karawang in dealing with drugs in the realm of education